NEW PUBLIC MANAGEMENT PARADIGM IN INDONESIA (LITERATURE STUDY) - Djoni Tepu; La Ode Muhammad Ichwan Sjachrawy; Maudhy Satyadharma; Neni Susanti (Yayasan Pendidikan Literasi Borneo, 2025)
New Public Management (NPM) emerged as a response to the weaknesses of traditional public administration, which was considered inefficient, by emphasizing efficiency, accountability, performance orientation, and public satisfaction. In the Indonesian context, post-Reformasi reforms became an important momentum for adopting NPM principles in various public sectors such as health, transportation, and governance. However, this transformation process faced various challenges, including bureaucratic rigidity, limited institutional capacity, regulatory constraints, and resistance to change. This study examines the implementation of the New Public Management (NPM) paradigm in Indonesia through a literature study approach. Through an analysis of various academic sources, this study discusses how NPM was institutionalized, its impact, and the factors that influenced its success. The study results found several discussion points from the literature raised, namely thematic convergence in the implementation of New Practice Management, the focus on leadership, governance, and human resources as driving and inhibiting factors, several analyses on specific sectors such as transportation, health, and encouraging anti-corruption, and the persistence of gaps in institutions.